Visualize neuronal membrane cholesterol with split-fluorescent protein tagged YDQA sensor - Yi Xu; Saixuan Li; Yiran Xu; Xiaoqin Sun; Yuqing Wei; Yuejun Wang; Shuang Li; Yongqi Ji; Keyi Hu; Yuxia Xu; Cuiqing Zhu; Bin Lu; et al. (Journal of Lipid Research)
Cholesterol is a major component of the cellular plasma membrane (PM), and its homeostasis is essential for brain health. Dysregulated cholesterol homeostasis has been strongly implicated in the pathogenesis of various neurological disorders, including Alzheimer’s disease (AD). However, in vivo visualization of cholesterol has remained challenging, hindering a comprehensive understanding of AD pathology. In this study, we generated a new sensor combining the split-fluorescent protein tags with YDQA, a derivate of cholesterol-dependent cytolysin PFO. Through a series of validations in cell and C. elegans models, we demonstrate that the new sensor (name as sfPMcho) efficiently detects neuronal PM cholesterol. We further applied this sensor in 5X FAD and APOE KO mice models and revealed the cholesterol changes within neurons. PM cholesterol became sparse and locally aggregated in neuron bodies but significantly accumulated in nerve fibers. Collectively, this study provides a new tool for detecting neuronal PM cholesterol in vivo and uncovers cholesterol abnormalities in AD-related pathology at the cellular level. Further development based on this sensor or a similar strategy is to be expected.